A Highly Birefringent and Nonlinear AsSe $_2$ –As $_2$ S $_5$ Photonic Crystal Fiber With Two Zero-Dispersion Wavelengths - Tianyu Yang; Can Ding; Y. Jay Guo (IEEE Photonics Journal, 2019)
A hybrid AsSe $_2$ –As $_2$ S $_5$ photonic crystal fiber (PCF) with a solid elliptical core is proposed and studied theoretically by the full-vector finite element method. The core and cladding of the PCF are made of AsSe $_2$ and As $_2$ S $_5$ glasses, respectively. Simulation results demonstrates that, at the operating wavelength of 1.55 $μ$ m, the proposed PCF not only exhibits a very high birefringence of 0.091 but also has large nonlinear coefficients of 147.8 and 78.2 $W^{-1}m^{-1}$ for the X- and Y-polarized (X and Y-pol) modes, respectively. Moreover, it is able to achieve two zero-dispersion wavelengths for both the X-pol (1.52 and 2.19 $μ$ m) and Y-pol (1.43 and 2.12 $μ$ m) modes. The proposed hybrid PCF exhibits excellent polarization maintaining and the nonlinearity performance, thus, suitable to be used in supercontinuum spectrum generation and polarization maintaining nonlinear signal processing.